The treatment of falciparum malaria. - White, N (1988)
Effective treatment for falciparum malaria has been available for over 300 years, and for most of this time physicians have argued over the best doses and the methods of administering antimalarial drugs. A reasonable consensus has since emerged on the treatment of uncomplicated malaria, but there is still disagreement over the management of severe infections, and as a consequence there have been confusing and dangerous discrepancies in treatment recommendations. In this review, Nicholas White discusses the confusion, offering a rational basis for the clinical treatment of both uncomplicated and severe falciparum malaria.